Legal Analysis Of Explicit Costs On Corruption In Indonesia In The Islamic Law Prespective - Andry Syafrizal Tanjung (Proceeding International Seminar of Islamic Studies, 2019)
The community-state established by the Prophet has provided some background and initial models of instruments and institutions which have become important pillars of the existence of a state-society. So if in the perspective of modern state administration know the three institutions of State power or what is called the trias politica namely the power of the legislative, executive and judiciary bodies, it turns out that the Prophet Muhammad SAW had practiced these three forms of institution. The existence of a fair nature is a matter of politics, meaning that there is no necessity in political matters to adhere to the constitutional principle that the suspect is clean of all accusations until there is evidence to prove that he is guilty, that is the basis for the realization of justice in justice. Corruption is an extraordinary crime, has a systemic and broad impact and has been placed as a violation of the people's economic and social rights. Therefore, the imposition of criminal sanctions related to the compensation of the state is not only the financial loss of the state in the event of a criminal act of corruption but must pay attention to explicit costs as part of the social costs of corruption caused by corruption. The explicit costs consist of anticipation costs of corruption, costs due to and reactions to corruption. Not only is punishment as a deterrent effect or a state financial return solely that it views it from the law on the eradication of corruption by horse glasses, but it must be viewed from the aspect of the benefit of the Indonesian people as direct victims of corruption. So what must be achieved is